Radio Komunitas dan Potensi Konflik Horizontal - Lukas Deni Setiawan (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2013)
Multiculturalism brings blessing and a negative potential. Blessed are the guidelines to respect the identity and rights of every community. Negative potential appears when the award is meant as a legitimacy to the arrogance of certain communities. This multicultural society dilemma accompany growth and development of Community Radio in Indonesia. On the one hand, the community is responding positively presence as a grassroots media speaker. But on the other hand, these conditions led some groups to disseminate the ideology of the group through the use of publicly owned frequencies. If the other side is more prominent, the potential for conflict between groups also became stronger.